Utilization of tanniniferous feeds. 6. Chemical composition, tannin fractionation, in vitro digestibility and gas production of some top foilage - BARMAN, K; RAI, S N (The Indian Journal of Animal Sciences, 2011)
Top foliages namely Robinia pseudoacacia (Robinia), Fiscus religiosa (Pipal) and Quercus incana (oak) were evaluated for chemical composition, tannin fractionation, in vitro digestibility of nutrients and gas production. Crude protein was higher in Quercus incana followed by Robinia pseudoacacia and Fiscus religiosa. Nitrogen free extract content was ranged from 36.2 to 59.4%. Total tannin (tannic acid equivalent) and condensed tannin (leucocyanidin equivalent) content was in the order of Quercus incana>Robinia pseudoacacia> Fiscus religiosa. In vitro dry matter, organic matter and gas production was higher in Fiscus religiosa; followed by Robinia pseudoacacia and Quercus incana.In vitro crude protein digestibility was in the order of Fiscus religiosa > Quercus incana >Robinia pseudoacacia. It is concluded that Robinia pseudoacacia and Fiscus religiosa may be used as a maintenance fodder for livestock while Quercus incana can be used as a lowgrade fodder in hilly areas where there is scarcity of fodders.Â